Environmental risk factors in primary liver cancer: a review of the literature and perspectives for primary prevention and early detection - Degli Esposti, Davide; Pham, Patrick; Saffroy, Raphaël; Azoulay, Daniel; Debuire, Brigitte; Lemoine, Antoniette (European Journal of Oncology and Environmental Health, 2014)
Primary liver cancer is a major public health problem, accounting for about 600,000 deaths in the world annually, with hepatocellular carcinoma (HCC) accounting for about 80% of all primary tumours in the liver and intra-hepatic cholangiocarcinoma (ICC) representing about 10-15% of the remaining primary hepatic malignancies. Incidence and mortality trends for both HCC and ICC are increasing globally, with particular concern for US and Europe, and survival rates are still very poor. Some risk factors are well-established, such as hepatitis viruses, alcohol intake and aflatoxins exposure for HCC, and infection with liver flukes and primary sclerosing cholangitis for cholangiocarcinoma (CC). However, these known etiologies do not explain the observed increased incidence of these two malignancies worldwide. Environmental carcinogens could play an underestimated rôle in the increased global burden of primary liver cancers. An essential tool to identify chemical and physical carcinogenic agents is long-term carcinogenicity bioassays, such as those performed by the US National Toxicology Program and the Ramazzini Institute. Although some strains of rodents are reported to be more susceptible to chemical-induced hepatocarcinogenicity, many similarities in histologic, cytological and molecular pathways are shared between humans and rodents in liver tumorigenesis, thus making long-term carcinogenicity bioassays the best available tool for identifying environmental carcinogenic agents, including those targeting the liver. Moreover, early detection of HCC and CC should provide a valuable means to decrease mortality rates in the short term, but reliable biomarkers are not yet available for clinical practice. Advanced technologies such as proteomics and in vivo imaging techniques are now available for animal cancer models. Well-designed protocols which will integrate a proteomic approach with imaging diagnostics using animal models may result in greater improvement for biomarkers development in early diagnosis of primary liver cancers.